1996
DOI: 10.1007/pl00004907
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of palytoxin-induced cation currents and Ca2+ mobilization in smooth muscle cells of rabbit portal vein

Abstract: We examined the nature of the palytoxin (PTX)-induced channel and its relevance to the Ca2+ mobilizing effect of the toxin on smooth muscle cells isolated from rabbit portal vein using whole-cell voltage-clamp and microfluorimetric techniques. PTX (1 nM) induced a sustained, irreversible inward current at a holding potential of -40 mV. The PTX-induced current reversed at 0.5 +/- 0.6 mV, and the PTX-induced channel permitted the passage of Na+, K+, Cs+ and, to a lesser extent, Li+, but not choline+ or Ca2+. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
3
6
0
Order By: Relevance
“…The results obtained in this study suggest that depolarization is due to an increase in cytosolic Na + as a primary event in palytoxin and ostreocin‐D action. In agreement with this, stimulation of Na + entry induced by palytoxin has been described in several cellular models [11,12,28,29]. We also found an increase in cytosolic Ca 2+ induced by both toxins.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results obtained in this study suggest that depolarization is due to an increase in cytosolic Na + as a primary event in palytoxin and ostreocin‐D action. In agreement with this, stimulation of Na + entry induced by palytoxin has been described in several cellular models [11,12,28,29]. We also found an increase in cytosolic Ca 2+ induced by both toxins.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that the elevation of cytosolic Ca 2+ induced by palytoxin is dependent on extracellular Ca 2+ [12,17,18,[34][35][36]. Our assays using neuroblastoma cells also indicated that palytoxin, as well as ostreocin-D, evoked Ca 2+ entry from the external medium.…”
Section: Discussionsupporting
confidence: 72%
“…PTX has been reported to increase both cytoplasmatic Na + and Ca 2+ concentrations under physiological conditions. The PTX‐induced calcium increase has been attributed to the activation of voltage‐dependent Ca 2+ channels, reverse of the Na + /Ca 2+ exchanger, or Ca 2+ entry through PTX‐induced channels (Ozaki et al,1983; Monroe and Tashjian,1995; Ishii et al,1997a).…”
Section: Discussionmentioning
confidence: 99%
“…PTX‐induced rise in Ca 2+ has been shown to be partially inhibited by verapamil, supporting a role for voltage‐dependent calcium channels that seem to be activated by PTX‐induced depolarization of the plasma membrane, on PTX‐induced calcium mobilization. The reverse operation of the Na + ‐Ca 2+ exchanger has also been implicated in the PTX‐induced calcium increase (Ozaki et al,1983; Ishii et al,1997a,b). In spite of the fact that PTX is not specific for the sodium pump and blocks also the H + ‐K + ‐ATPase (Scheiner‐Bobis et al,2002), other factors that could contribute to calcium accumulation such as inhibition of the calcium‐ATPase (Garcia and Strehler,1999) have not yet been investigated.…”
mentioning
confidence: 99%
“…Palytoxin (PTX), isolated from Palythoa spp., is the most potent marine toxin known. We have reported that PTX induces a cation channel, which is permeable to monovalent cations, in cardiac ventricular or vascular smooth muscle cells [1–3]. Its lethal action is ascribed to an increase in cytosolic Na + concentration and the subsequent increase in cytosolic Ca 2+ [4].…”
Section: Introductionmentioning
confidence: 99%